PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN MENGGUNAKAN ALAT PERAGA DAKOTA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 119 PEKANBARU - Ulfa, Yunita; Witri, Gustimal; N, Lazim. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the number of students who do not understand the concept of mathematics learning especially on KPK and FPB material well, so the value of mathematics learning result of students is still relatively low. Data obtained from the observation results in the know that the value of mathematics KKM in the school set is 72. The number of students who reach KKM is only 6 of 23 people or only 26.08%, while the number of students who have not reached the KKM of 17 people or equal to 73.92%. . Based on this problem, the action taken is cooperative learning with dakota props. The purpose of this research is to improve students' mathematics learning outcomes. This form of research is a classroom action research. The subject is the students of grade IVA at SDN 119 Pekanbaru, consisting of 23 students; 10 men and 13 women. The research instruments are test sheets, teacher and student observation sheets, and documentation files. The results show an improvement over each cycle. Teacher activity in the first cycle was 54.15%, and increased to 77.15%. In cycle II was 87.5%, and increased to 95.83%. Student activity in cycle I was 54.15%, and increased to 62.5%. In cycle II was 87.5%, and increased to 95.83%. The student's average score also shows improvement. The base rate is 62.30; increased to 88.13 at UH I, and increased to 91.73 in UH II. Based on these results, it can be concluded that the application of cooperative learning model with Dakota props can improve student learning outcomes of class IVA in SDN 67 PekanbaruKeyword : Cooperative learning,dakota props mathematics grade